Review on Corosolic Acid:Based on Various Pharmaceutical Effects - Park, Cheolin; LEE’s, Jae Sik (Asian Journal of Pharmaceutical Research and Development, 2019)
Corosolic acid is a pentacyclic triterpene acid found in banaba leaves, Lagerstroemia speciosa which is similar in structure to useful pharmaceutical material such as ursolic acid and has been reported to have beneficial activities, as found in in vitro and several animal studies including human studies, particularly due to its effects on lowering of blood sugar. This review paper is focused on various pharmaceutical effects including decreasing of blood sugar of corosolic acid from published articels and can be helpful on the understanding of those effects which can be appliable on maintenace and treatment against several diseas